2018
DOI: 10.14202/vetworld.2018.1214-1221
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, toxigenic potential and antimicrobial susceptibility profile of Staphylococcus isolated from ready-to-eat meats

Abstract: Aim:An epidemiological surveillance for Staphylococci contamination of ready-to-eat (RTE) meats from Enugu State, Nigeria, was carried out to determine the prevalence, species distribution, toxigenic potential and antimicrobial susceptibility profile of the organisms and hence the microbiological and toxicological safety of the meats.Materials and Methods:Isolation and phenotypic Staphylococcus detection were done according to standard microbiological methods. Phenotypic resistance to 17 commonly used antimicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 26 publications
(45 reference statements)
1
16
1
Order By: Relevance
“…A lower (27.9%) and higher (68.00%) incidences of Staphylococcus aureus were reported by Ge et al (2017) in the USA and Tang et al (2017) in Denmark, respectively, in retail meats. The prevalence of Staphylococcus aureus in ready-to-eat pork and ready-to-eat chevon collected from Enugu State, Southeast Nigeria was 4.2% and was 5.9%, respectively (Okoli et al, 2018), which were lower than the 24% each observed for ready-to-eat pork and ready-to-eat chevon in this study. Also, the prevalence of Staphylococcus aureus in ready-to-eat pork was 12.7% and that of ready-to-eat mutton was 0% in China (Wu et al, 2018) which were lower as compared to this study.…”
Section: Incidence Of Staphylococcus Aureus In Ready-to-eat Meatscontrasting
confidence: 76%
“…A lower (27.9%) and higher (68.00%) incidences of Staphylococcus aureus were reported by Ge et al (2017) in the USA and Tang et al (2017) in Denmark, respectively, in retail meats. The prevalence of Staphylococcus aureus in ready-to-eat pork and ready-to-eat chevon collected from Enugu State, Southeast Nigeria was 4.2% and was 5.9%, respectively (Okoli et al, 2018), which were lower than the 24% each observed for ready-to-eat pork and ready-to-eat chevon in this study. Also, the prevalence of Staphylococcus aureus in ready-to-eat pork was 12.7% and that of ready-to-eat mutton was 0% in China (Wu et al, 2018) which were lower as compared to this study.…”
Section: Incidence Of Staphylococcus Aureus In Ready-to-eat Meatscontrasting
confidence: 76%
“…This could be from direct human contacts such as fingers or indirectly through additives or utensils. The result is in agreement with the results of [28]. They reported that 9.4% of ready-to-eat-food meats sampled were contaminated with toxigenic and multidrug resistance CoNS.…”
Section: Discussionsupporting
confidence: 91%
“…This may also be found in external body surfaces as either commensal or pathogenic bacteria that can cause multiple infectious diseases (Weese and van Duijkeren, 2010). S. aureus has a variety of virulence factors and toxins, frequently responsible for many toxin-diseases including toxic shock syndrome, staphylococcal foodborne diseases (SFDs), and scalded skin syndrome (Okoli et al, 2018). Staphylococcus has the potential to establish resistance to broad-spectrum antibiotics in a short period, such as the β-lactam group of antibiotics, aminoglycosides and quinolones commonly used in clinical practice for the treatment of serious infections (Deurenberg et al, 2007).…”
Section: Introductionmentioning
confidence: 99%